Qualitative Analysis of Malaria Cases Reported at a Tertiary Care Hospital in Ahmedabad: A Record Base Study - Chaudhari, Rajkamal; Mod, Jaydev; Parikh, Sonal; Rajendran, Santhosh (National Journal of Community Medicine, 2017)
Introduction: Malaria is a life threatening parasitic disease caused by parasites known as Plasmodium vivax, Plasmodium falciparum, Plasmodium Ovale and Plasmodium malariae. P.falciparum and P.vivax are equally prevalent in India.In India about 95% of the population resides in malaria endemic area. Objectives: To study the clinical profile of malaria at tertiary care hospital. Method: A retropective study was conducted in V.S.Hospital Ahmedabad, a tertiary care hospital January 2016 to December 2016. This study included 491 patients of age 13 years and above with either a smear positive for plasmodium species or malarial antigen positive by RDT (rapid diagnostic test) admitted in the hospital. Results: Total 491 patients were admitted with malaria in v.s. hospital during the year of 2016, out of which 352 (71.69%) cases were positive for P.Vivax malaria, 109 (22.19%) were positive for P.Falciparum malaria and 10 (2.0%) cases were positive for both species. Total 20 (4.07 %) patients expired. Conclusion: Although P. vivax was the commonest species affecting the population , P. falciparum cases were more complicated and were associated with higher morbidity and mortality. Malaria presented with multi organ involvement had poor prognosis.